Influence of reef cover classes on functional diversity of reef fish in the Banyak Islands Marine Nature Park, Aceh Province, Indonesia (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Nasution MA, Najmi N, Hermi R, Lubis F, Lisdayanti E, Saputra F. 2025. Influence of reef cover classes on functional diversity of reef fish in the Banyak Islands Marine Nature Park, Aceh Province, Indonesia. Biodiversitas 26: 4346-4362. Coral reefs are critical marine ecosystems that are increasingly threatened by human and environmental pressures, prompting research into how habitats shape biodiversity. This study explored how seven reef cover classes: reef slopes, sheltered reef slopes, reef crests, reef flats, plateaus, backreef slopes, and lagoons, influence reef fish functional diversity in the Banyak Islands Marine Nature Park, Aceh Province, Indonesia. Using underwater visual censuses across 20 sites with 60 belt transects (250 m² each), we surveyed 131 reef fish species at 3-12 m depths. We measured four functional diversities of reef fish: Functional Richness (FRic), Functional Divergence (FDiv), Functional Evenness (FEve), and Rao’s Quadratic entropy (RaoQ). Bayesian multivariate models revealed that reef slopes, sheltered reef slopes, and reef crests significantly influenced functional diversity, explaining 2-55% of variance, average 28.5%. Reef slopes showed the strongest effects, positively influencing FEve (posterior probability: 0.95) and RaoQ (posterior probability: 0.99), indicating balanced trait distribution and enhanced functional diversity in structurally complex habitats. However, reef slopes negatively affected FDiv (posterior probability: 0.89). Reef slopes notably boost RaoQ and FEve, reflecting balanced trait distribution and diverse ecological roles. The effects on functional richness and divergence were less pronounced, indicating limited trait range expansion. This study reveals that certain reef formations play a crucial role in maintaining healthy aquatic ecosystems, which is vital for conservation efforts in less-than-ideal reef environments.
Keywords: Banyak Islands, functional diversity, reef cover class, reef fish, reef slopes